1983
DOI: 10.1111/j.1365-2621.1983.tb09181.x
|View full text |Cite
|
Sign up to set email alerts
|

Residence Time Distributions for Wheat Starch in a Single Screw Extruder

Abstract: Residence time distributions for wheat starch in a single screw exnuder were measured for different operating conditions using a manganese dioxide tracer. Two flow models which differed in the definition of dead space were used to represent the flow pattern in the extruder. The parameters for each model were fitted using the experimental residence time distributions. Screw speed and the moisture level of the feed showed the strongest effects on the average residence time. A small fraction of the flow, 5-20%, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
3

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 7 publications
3
35
3
Order By: Relevance
“…However, the effect on variance was not quiet clear. Davidson, Paton, Diosady, and Spratt (1983), Lee and McCarthy (1996), Todd (1975), and Yeh et al (1991) had reported similar results. Increased screw speed may have resulted in more viscous heat dissipation, greater pumping force and more shearing, which enabled shorter MRT and better mixing of the material.…”
Section: Effects Of Screw Speedmentioning
confidence: 59%
“…However, the effect on variance was not quiet clear. Davidson, Paton, Diosady, and Spratt (1983), Lee and McCarthy (1996), Todd (1975), and Yeh et al (1991) had reported similar results. Increased screw speed may have resulted in more viscous heat dissipation, greater pumping force and more shearing, which enabled shorter MRT and better mixing of the material.…”
Section: Effects Of Screw Speedmentioning
confidence: 59%
“…Decreasing the screw speed increases the residence time and induce a higher degree of fill. This effect pushes the biomass across restricting elements more slowly, thus higher pressures can be developed [4,30]. The SME did not seem to be affected by the screw speed (decreased torque at higher rotation) as shown in Fig.…”
Section: The Effects Of Operating Conditions On Xylose Recoverymentioning
confidence: 83%
“…where (4) Hence, the four parameters that fully represent this model are t ‾, p, n and d. Other proposed models were described and compared by Davidson et al (1983).…”
Section: E(t) and F(t)mentioning
confidence: 99%
“…The complete model is the most general model among all proposed models described in detail by Davidson et al (1983). The model represents the WolfResnich model when the plug flow fraction (p) is zero, the Levich model when n is very large and dead volume fraction (d) is zero, and the simplified model when the value of n is one.…”
Section: Comparison Of Modelsmentioning
confidence: 99%
See 1 more Smart Citation